Digital Transformation Model of Population Administration Services for Regional Development through a Population Data Utilization System in Medan City - Admar, Adisti Maritadinda; ., Sirojuzilam; ., Badaruddin; ., Rujiman (Journal of Ecohumanism, 2024)
This research aims to examine the influence of digital transformation on population administration services and its implications for regional development in Medan City. Against the background of the need to increase the efficiency and effectiveness of public services, this research adopts a quantitative approach, using tools such as questionnaires, in-depth interviews and observations to collect data. Against the background of the need to increase the efficiency and effectiveness of public services, this research adopts a quantitative approach, using tools such as questionnaires, in-depth interviews and observations to collect data. The research results indicate that digitalization of population services makes a positive contribution to improving the quality of public services, which indirectly influences regional development through increasing efficiency, accessibility and transparency of services. And this research provides insight into e-government strategies in Medan, supporting the effective use of population data in supporting inclusive and sustainable regional development.